Control of quiescence and activation of human muscle stem cells by cytokines - Katharine Striedinger; Emilie Barruet; Elena Atamaniauc; Karla Linquist; Chris Knott; Andrew Brack; Jason H. Pomerantz (PLoS ONE, 2025)
Skeletal muscle homeostasis and repair depend on the activation of tissue resident stem cells called satellite cells. To understand the early molecular basis of human satellite cell activation, epigenomics, transcriptomics and protein analysis were performed in quiescent and experimentally activated human satellite cells. Cytokine signaling pathways were enriched in activated human satellite cells revealing high cytokine enrichment, including CCL2, CCL20, CXCL8, IL-6, TNFRSF12A, ILR1, CSF-1 and FGF2. Functional roles of these observed changes are supported by in vivo experiments showing that chemokine inhibitors increase engraftment and regeneration capacity of human satellite cells xenotransplants. Cytokines, chemokines and associated signaling pathways in the early stages of human satellite cell activation may underlie disparate muscle responses in neuromuscular inflammatory and degenerative disorders and consequently are potential entry points for clinical applications towards muscle repair.